Intensificação da produção de ovinos em um sistema agrossilvipastoril da região do Baixo Parnaíba maranhense - Sousa, Carlos César Martins de (2017)
The way of meeting the demand for food, bioenergy and forest products has caused negative impacts to the environment in recent times, due to inadequate soil management and, as a consequence, caused low agricultural productivity. Intensifying land use in agricultural areas and increasing the efficiency of production systems can contribute to reducing these negative effects. The objective of this work was to evaluate the effect of legumes on weight gain in sheep finishing in an agrosilvipastoril system, located in the village of Campamento, municipality of Brejo - MA. In January 2017 AG 1051 maize and mombaça grass were planted among four tree legume species: leucena, acacia, sombreiro and gliricídia, established in an area of 14,875 m² since 2011. Five maize silage-based diets with and without legumes (M + A, M + S, M + L, M + G and Control) were produced from maize cultivated. The evaluated parameters of the analyzed material, legumes, mombaça grass and silages were: dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), organic matter mineral (MM). The diets produced were tested on 20 castrated lambs (SRD with Santa Inês), mean PV (20.63 ± 1.54 kg). A completely randomized experimental design with five treatments and four replications was used. The daily weight gain (GPG) of the sheep was measured. The legumes added to the soil increased the DM yield of the mombaça grass and corn silage ha-1 and, added to the sheep diet, promoted contribution in the PB levels and increased the weight gain of these animals and, therefore, is an important alternative for the nutrient increment in feed of sheep finished in agrosilvipastoril system and can be a viable alternative for the integrated systems of integrated production of the humid tropic.